2005
DOI: 10.1287/mnsc.1050.0429
|View full text |Cite
|
Sign up to set email alerts
|

Investment Decisions and Time Horizon: Risk Perception and Risk Behavior in Repeated Gambles

Abstract: To investigate the effect of time horizon on investment behavior, this paper reports the results of an experiment in which business graduate students provided certainty equivalents and judged various dimensions of the outcome distribution of simple gambles that were played either once or repeatedly for 5 or 50 times.Systematic mistakes in the ex-ante estimations of the distributions of outcomes after (independent) repeated plays were observed. Despite correctly realizing that outcome standard deviation increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 42 publications
8
84
0
1
Order By: Relevance
“…Based on currently available risk reduction rates, few women, regardless of fracture risk, would choose rhPTH (1-34) over other treatment options. Subjects at risk for future osteoporotic fractures were willing to take rhPTH (1-34), but most demanded efficacy advantages greater than that demonstrated in clinical trials to date [10,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on currently available risk reduction rates, few women, regardless of fracture risk, would choose rhPTH (1-34) over other treatment options. Subjects at risk for future osteoporotic fractures were willing to take rhPTH (1-34), but most demanded efficacy advantages greater than that demonstrated in clinical trials to date [10,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of women (regardless of risk) preferred rhPTH (1-34) over bisphosphonates as the efficacy of teriparatide increased (see Figure 1). However, rhPTH (1-34) became the preferred treatment option for the majority of respondents only when it is described as having benefits far greater than expected based on results of randomized trials ( Figure 1) [10,[31][32][33].…”
Section: Treatment Preferencesmentioning
confidence: 99%
“…In the single-application task, the selected risky option is only applied once; in the multiple-application task, the selected risky option is applied 100 times. Empirical research found that the behaviour of decision makers in multiple-application gambles is consistent with the predictions of compensatory theory (Colbert et al, 2009;DeKay et al, 2006;Keren, 1991;Klos, Weber, & Weber, 2005;Langer & Weber, 2001;S. Li, 2003;Redelmeier & Tversky, 1992;Wedell & Böckenholt, 1994).…”
Section: Single-application Versus Multiple-application Methodsmentioning
confidence: 55%
“…Second, the elicited quantiles must be ordered in a consistent way: participants cannot switch from Security A to B1 at a threshold that exceeds the threshold at which she switches from Security A to B2, which in turn cannot exceed the threshold at which she switches from Security A to B3. 18 Participants receive a participation fee of £5 and a possible bonus of £5 per round. In each round, a single choice is randomly determined to be payoff-relevant, giving an ex-ante incentive to act optimally in each task.…”
Section: Experimental Designmentioning
confidence: 99%
“…17 All participants passed the understanding test, in a few cases after asking for some additional explanations. 18 The instructions explain that violations of these constraints are subjectively suboptimal. Additionally, the experimental software shows an error message if a participant violates either of the two constraints.…”
Section: Linearity Bias Predictionmentioning
confidence: 99%